Women’s Struggle in Poetry Collection Milk and Honey by Rupi Kaur (2011) - Qolbia, Annisa; Hafizh, Muhd Al (English Language and Literature, 2024)
This research is an analysis of the poetry collection Milk and Honey by Rupi Kaur (2011). This analysis is only carried out in 2 chapters, namely the hurting and the healing chapter. This research examines several forms of gender inequality and forms of women struggle’s struggles to get out of this gender inequality. The form of gender inequality contained is in the form of harassment experienced by women. This research also discusses the form of women’s struggle in obtaining freedom and happiness. Researchers’ uses qualitative descriptive techniques using feminist theory that can make women free to get happiness. The result of this study indicate that women are able to change the situation by fighting the injustice they experience and are able to stand alone without a man in their life.